Unveiling cellular communications through rapid pan-membrane-protein labeling - Hirushi Gunasekara; Yu-Shiuan Cheng; Vanessa Perez-Silos; Alejandro Zevallos-Morales; Daniel Abegg; Alyssa Burgess; Liang-Wei Gong; Richard D. Minshall; Alexander Adibekian; Carlos Murga-Zamalloa; Alison E. Ondrus; Ying S. Hu (Nature Communications)
Abstract Dynamic protein distribution within and across the plasma membrane is pivotal in regulating cell communication. However, rapid, high-density labeling methods for multiplexed live imaging across diverse cell types remain scarce. Here, we demonstrate N-hydroxysuccinimide (NHS)-ester-based amine crosslinking of fluorescent dyes to uniformly label live mammalian cell surface proteins. Using model cell systems, we capture previously elusive membrane topology and cell-cell interactions. Live imaging shows transient membrane protein accumulation at cell-cell contacts and bidirectional migration patterns guided by membrane fibers in DC2.4 dendritic cells. Multiplexed superresolution imaging reveals the biogenesis of membrane tunneling nanotubes that facilitate intercellular transfer in DC2.4 cells, and caveolin 1-dependent endocytosis of insulin receptors in HEK293T cells. 3D superresolution imaging reveals membrane topology remodeling in response to stimulation, generation of microvesicles, and phagocytic activities in Jurkat T cells. Furthermore, NHS-labeling remains stable in vivo, enabling visualization of intercellular transfer among splenocytes using a T cell lymphoma mouse model.